(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The development of competent green chemistry methods for synthesis of metal nanoparticles have become a main limelight of researchers in the field of nanotechnology.Nanoparticles are advanced matarials have recently gained high attention due to their scientific and technological important. They find awide variety of applications such as catalysts with huge activity and specificity,metal semiconductor In this thesis, preparation compound ( CuFe2O4@SiO2-PA-TFA MNPs ) synthesized CuFe2O4@SiO2 functionalized with propylamine and trifluoroacetic acid. Heterocycle compounds are an important compound of organic chemistry that exist in the structure of natural products and are responsible for the biological and pharmacological properties of most medicinal compounds. Characterization of CuFe2O4@SiO2-PA-TFA MNPs was performed by SEM, EDX, XRD, TGA and VSM analysis. Application of these nanoparticles in the synthesis of tetrahydropyrazolopyridines, shown high activity of the catalyst.